Relationship between cancer related fatigue, physical activity related health competence, and leisure time physical activity in cancer patients and survivors - Köppel, Maximilian; Körbi, Carlotta; Winkels, Renate M.; Schmitz, Kathryn H.; Wiskemann, Joachim (Frontiers in sports and active living, 2021)
Background: A large body of evidence supports the positive effects of leisure time physical activity (LTPA) and exercise on cancer survivors. However, only a fraction of survivors manages to attain international PA recommendations. This can be attributed to several external and internal barriers toward PA those patients seem to encounter, with cancer related fatigue (CRF) being the most reported internal barrier. Nevertheless, self-efficacy and knowledge about the utilization of LTPA can serve as facilitators of PA, which also correspond to certain constituents of physical activity related health competence (PAHCO). Since PAHCO is not investigated in cancer survivors we investigated if PAHCO can mediate the negative relationship between CRF and LTPA.Methods: We surveyed 398 cancer survivors with different cancer types and therapy status. The patients completed the EORTC QLQ-FA12 (EORTC FA12) to assess CRF, the PAHCO questionnaire to assess PAHCO and the SQUASH to assess LTPA. We followed a two-step structural equation modeling approach. The first step established the measurement model, in the second step we fitted the mediation model. Since 163 patients chose not to answer the SQUASH, the mediation model was only fitted to the data of the remaining 235 participants.Results: The proposed measurement model of the PAHCO offered an excellent fit. We found small to moderate positive associations between the PAHCO dimensions and the LTPA, and negative moderate relationships between the PAHCO and the EORTC FA12 dimensions. We did not observe a relationship between the EORTC FA12 dimensions and the LTPA (p > 0.05). The hypothesized mediation models did not display an appropriate fit.Conclusion: The PAHCO confirmed its factorial validity; furthermore, it appears to have a positive relationship to LTPA. Therefore, integrating psycho-educational aspects can be beneficial in order to increase the PAHCO in exercise interventions. Because of the cross-sectional character of this study, causal conclusions are not suitable, therefore the longitudinal relationships of LTPA, CRF, and PAHCO require further investigation.
Gesehen am 26.08.2021